SAMR 2022
DOI: 10.57044/samr.2022.1.1.2206
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Green Supply Chain Management on Sustainable Performance

Abstract: This study examines the influence of green supply chain management on sustainable performance. The natural resource-based theory was tested on manufacturing firms in Karachi, Pakistan. A quantitative approach was adopted for this study, and a multi-item measurement scale was adapted from previous studies. A structured questionnaire was developed to collect primary data—the total number of 224 responses collected from textile manufacturing firms. Structural equation modeling was applied for hypothesis testing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Afterwards, AMOS and SPSS software was chosen to analyze the gathered data for this study to determine the impact of JIT production on organizational performance. This study found a direct and highly positive impact of the integration of JIT production on both the operational as well as the financial performance of an organization (Muzammil, 2022;Basit, 2022).…”
Section: Jit and Performancementioning
confidence: 66%
“…Afterwards, AMOS and SPSS software was chosen to analyze the gathered data for this study to determine the impact of JIT production on organizational performance. This study found a direct and highly positive impact of the integration of JIT production on both the operational as well as the financial performance of an organization (Muzammil, 2022;Basit, 2022).…”
Section: Jit and Performancementioning
confidence: 66%
“…"Class B" items are the second-most essential, while "Class C" goods are the least significant. Other businesses may choose a categorization scheme that divides things into more categories than those three (Basit, 2022;Cole & Stuart, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When partners work together with other parties to make sure that their supply chain can respond to changing market demands, collaboration has a significant potential to improve business performance (Byrne et al, 2018;Basit, 2022). It includes managing connections with suppliers and buyers both upstream and downstream in order to provide better customer value at a lower cost to the supply chain.…”
Section: Literature-reviewmentioning
confidence: 99%